2022
DOI: 10.3389/fpsyg.2022.917039
|View full text |Cite
|
Sign up to set email alerts
|

Does Internet Connect to Social Justice Perception in China?

Abstract: The world has witnessed an important and dramatic transition during the past decades, with social and economic challenges related to the advancement of digital technologies. Meanwhile, inequalities of distributions of resources and opportunities obstinately exist around the world. This study innovates by utilizing household survey datasets to empirically evaluate the impact of Internet utilization on individual’s perception toward social justice in China. Estimates suggest that Internet utilization generates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Considering the data characteristics of the explained variables, we referred to Zhou et al (2022) and ran Ordered Probit model to analyze and estimate the effect of the Internet on SWB of the elderly. The model settings are as follows:…”
Section: Empirical Analytic Strategies and Estimation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the data characteristics of the explained variables, we referred to Zhou et al (2022) and ran Ordered Probit model to analyze and estimate the effect of the Internet on SWB of the elderly. The model settings are as follows:…”
Section: Empirical Analytic Strategies and Estimation Resultsmentioning
confidence: 99%
“…Considering the data characteristics of the explained variables, we referred to Zhou et al (2022) , .…”
Section: Empirical Modelmentioning
confidence: 99%
“…The possible reason for this is that the Internet expands people's objects of reference, and the expansion of upward comparisons increases people's sense of relative deprivation [34] (Xie et al, 2022). At the same time, the Internet provides more information and facilitates social interaction, increasing the unfairness people observe and the probability of experiencing it [45] (Zhou et al, 2022). These may be the reasons why internet use reduces the perception of social fairness.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…[45][46](Xie et al, 2022;Zhu et al, 2020;Zhou et al, 2022). In terms of impact mechanisms, researchers have found that Internet use may lead to a decline in the perception of social fairness by reducing people's sense of income equity and class mobility[47] (Li et al, 2023) and may also lead to a reduced perception of social fairness by increasing individuals' tendency to make outward-looking attributions[48] (Han and Pan, 2023).…”
mentioning
confidence: 99%
“…Due to the Internet widening the scope of social comparisons, it can generate a sense of relative deprivation and frustration that negatively affects mental health. With the perception of social fairness fades, psychological deficits, including a poor sense of self, unmet needs, and personal trauma, will be generated in the public, which may even trigger hatred in irrational scenarios ( 63 ). Following the above analysis, we propose H2d:…”
Section: Theoretical Underpinning and Hypothesis Developmentmentioning
confidence: 99%